A Comparative Study on Creative Self-Concept among Millennials and Gen Z - Mabagos, Ninna Loise R.; Mallari, Erika F.; Manabat, Ivan Remoh Q.; Maulas, Zairah C.; Mirando, May B.; Vergara, Jerald Q.; Cantilero , Kimberly Ann S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Creativity shapes how individuals solve problems, express themselves, and innovate. How individuals view creativity is vital as it shapes how they adapt, solve problems, and thrive in everyday situations. This study explored the creative self-concept of Millennials and Generation Z in Central Luzon, Philippines. Creative self-concept encompasses both creative self-efficacy and creative personal identity, referring to how individuals perceive their creativity. While generational differences in values and skills are widely studied, little is known about how Filipino Millennials and Generation Z perceive their creativity. Using a cross-sectional survey method, information was gathered from 300 respondents, evenly split between their generation group. The independent sample t-test revealed that there is no significant difference in creative self-concept between the participants’ generations (p = 0.19). Similarly, a non-significant result was also observed between respondents’ geographical locations (p = 0.12). However, results from ANOVA revealed that people with more schooling (F = 7.94, p < 0.001) had more creative ideas about themselves compared to those who had lower educational attainment. These results showed that educational experiences may have a bigger effect on how people think about creativity than their generational group or where they live. The study highlights the importance of incorporating activities that foster imagination in schools, enabling students of all ages to generate new ideas and feel confident in their abilities.